Rethinking the Evidence on COVID in Africa - Bejon, Philip; Agweyu, Ambrose; Oyier, Isabella; Hamaluba, Mainga; Kamuya, Dorcas; Kinyanjui, Sam; Barasa, Edwine (My University, 2024)
The COVID pandemic was predicted to cause substantial mortality in Africa. However, experiences from many countries in Africa were notable for a striking absence of overwhelmed hospitals, and for low reported mortality. The marked contrast with the overwhelmed hospitals and high mortality seen in Europe and other high income settings was regarded as “puzzling” or a “paradox”. We reflect on possible explanations for this paradox with particular reference to observations made “on the ground” in Kenya. We identify sufficient evidence to reject many potential explanations for the differing epidemiology in Africa. Longitudinal surveillance using antibody assays suggested that viral transmission was widespread and rapid. These data contradict explanations such as: an impact of climate on virus droplets; enhanced air circulation in rural settings; or stringent and effective public health interventions against infectious spread. We acknowledge resource limitations on surveillance of severe disease in hospitals and registration of deaths, but nevertheless identify sufficient evidence to exclude hidden hospital surges, and to exclude a hidden substantial death rate outside hospital. Population age structure is an important but incomplete explanation of the epidemiology. The simplistic calculation of multiplying infection-fatality rates by the Kenyan population age structure implies a figure substantially higher than the observed excess deaths, and the calculation is further misleading because the infection fatality rates were derived from settings where the health system capacity mitigated the risk of death. Multiplying infection-hospitalization rates by the age structure of the Kenyan population predicts over a million hospital admissions, which would have been well beyond the surge capacity of the Kenyan healthcare system, and incompatible with the data showing that substantial hospital surges were not seen. We found a very high prevalence of asymptomatic infection in routine data as well as in longitudinal studies with active surveillance. Taking this together with the lack of hospital surges, the low mortality estimates, and the evidence against reduced viral transmission, we conclude the primary explanation for the “paradox” is reduced susceptibility to symptomatic disease among populations in Africa. There is an opportunity to further study pre-pandemic immunity and other potential mechanisms for the reduced susceptibility to severe COVID in Africa. Given our incomplete understanding of the mechanisms associated with reduced susceptibility to severe COVID, we should not be complacent about health security in Africa, and should prioritize the rapid acquisition of data on the ground to guide future pandemic responses.
Keywords: COVID; Mortality; Policy; Susceptibility